The influence of leadership and communication on productivity with job satisfaction as an intervening variable - Oktavia Dian Maurisa Putri; Muhadar Putih (Jurnal Mantik, 2023)
Employee productivity is the main thing that must be achieved in order to maintain a company's reputation and business continuity. One of the factors that can increase work productivity is employee job satisfaction. Employee job satisfaction is always associated with a person's leadership style. Likewise with communication which is considered capable of influencing employee work satisfaction. The purpose of this research is to find out how leadership, communication and job satisfaction affect the productivity of PT Kao Indonesia Cikarang employees. This study used a simple random sampling technique, which was carried out randomly with a sample of 110 respondents. The approach used in this research is a quantitative approach. Data processing using SmartPLS Software. Based on all the tests that have been done, it is known that leadership has a positive and significant effect on job satisfaction because p-values are 0.013<0.050 with t-statistics 2.503>1.960, which means that the better the leader, the job satisfaction will increase. Communication also has a positive and significant effect on job satisfaction because p-values are 0.000<0.050 with t-statistics 4.056> 1.960, which means that the better the way of communicating, the job satisfaction will increase. Then leadership has no significant effect on employee productivity, as well as communication which has no significant effect on employee productivity because p-values > 0.050 and t-statistics <1.960. While job satisfaction has a positive and significant effect on employee productivity with p-values 0.000 <0.050 and t-statistics 3.773 > 1.960, which means that the higher the level of employee job satisfaction, the employee productivity also increases